CD48 and α7 Nicotinic Acetylcholine Receptor Synergistically Regulate FimH-Mediated Escherichia coli K1 Penetration and Neutrophil Transmigration Across Human Brain Microvascular Endothelial Cells. (10th September 2018) - Liu, Rui; Wu, Chao; Li, Li; Chi, Feng; Zhang, Tiesong; Xu, Yating; Ji, Lulu; Chen, Zhiguo; Hu, Hanyang; Zhang, Xiaoli; Huang, Shenghe; Wang, Lin
Abstract: FimH-mediated bacterial invasion and polymorphonuclear neutrophil (PMN) transmigration across human brain microvascular endothelial cells (HBMECs) are required for the pathogenesis of Escherichia coli meningitis. However, the underlying mechanism remains unclear. This study demonstrated that the TnphoA mutant (22A33) and FimH-knockout mutant (ΔFimH) of E coli strain E44, which resulted in inactivation of FimH, were less invasive and less effective in promoting PMN transmigration than their wild-type strain. FimH protein induced PMN transmigration, whereas calmodulin inhibitor significantly blocked this effect. Moreover, immunofluorescence and co-immunoprecipitation analysis indicated that colocalized CD48 and α7 nAChR formed a complex on the surface of HBMECs that is associated with increased cofilin dephosphorylation, which could be remarkably enhanced by FimH + E44. Our study concluded that FimH-induced E coli K1 invasion and PMN migration across HBMECs may be mediated by the CD48-α7nAChR complex in lipid rafts of HBMEC via Ca 2+ signaling and cofilin dephosphorylation. Abstract : FimH-induced E coli K1 penetration and PMN migration across HBMECs is mediated by the CD48-α7nAChR complex in lipid rafts of HBMECs through Ca 2+ signaling and cytoskeleton rearrangement.